Alternative investments: is it a solution to the funding shortage of US public pension plans?. (23rd October 2020) - Peng, Jun; Wang, Qiushi
Abstract: Since 2001, public-pension plans have increasingly relied upon alternative investments (AIs). We examine the impact of this trend on investment performance and the factors that led to the reliance on AI. Using data from 92 largest plans 2001–2014, we found AI, especially private equity, generally had a positive effect on investment performance, but the effect was small and unsustainable. We also found that plans with a lower funded ratio and higher investment return expectation were more likely to allocate more assets to AIs. These findings suggest that the prospect of relying on AIs to meet investment return expectations remains a long-term challenge for state and local governments.